A Comparison of Perinatal Outcomes of Turkish and Syrian Immigrant Women: A Case-Control Study - zehra incedal SONKAYA; Aksüt AKÇAY, Emine (International Journal of Computational and Experimental Science and Engineering, 2025)
This present aim the differences in prenatal, labor and neonatal outcomes for Syrian refugees and Turkish citizens. A total of 315 Turkish and 296 Syrian migrant women participated in the case-control study. Age, age at first pregnancy, antenatal care, and prenatal hemoglobin values were significantly lower in Syrian refugee group. Stillbirth rates were higher in the Turkish citizens group. The percentage of newborns hospitalized in a neonatal intensive care need and neonatal resuscitation was higher in Syrian immigrant women. In comparison to non-refugee control patients, refugee women in our study had poor antenatal care and adverse perinatal outcomes were observed.